THE DETERMINATION OF PARABEN PRESERVATIVES IN BODY SCRUB (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2019)
Esther alkyl of p-hidroksibenzoat (paraben) widely used as an agent antimikroba with activity antimikroba increase in line with the length of the chain alkyl. The compound is widely used as a preservative on scrubs to extend the savings products. Scrubs is one care products the body much used to lift sel-sel dead skin can replace the soap. Although beneficial as a preservative , research liaise paraben with some side effects adverse as cancer, infertility and miscarriage. The identification of the two kinds of paraben (metyl paraben and propyl paraben) of 10 sample wraps done with thin layer chromatography (TLC) who proceed to the analysis of the levels of parabens using spectrophotometer UV-Vis. The results showed that of the 10 samples there are 8 samples positive methyl paraben with average levels of value of 0.05% and 7 samples positive with propyl paraben are common values of average levels of 0.03%. The average total of paraben in sample 8 body scrub that is amounted to 0.08%. Comparison paraben shows that methyl paraben having concentration higher in any product.
Keywords: Paraben; Body Scrub; KLT; Spektrophotometer UV-Vis